2019
DOI: 10.1182/bloodadvances.2018028662
|View full text |Cite
|
Sign up to set email alerts
|

Racial disparities in access to HLA-matched unrelated donor transplants: a prospective 1312-patient analysis

Abstract: Availability of 8/8 HLA-allele matched unrelated donors (URDs) is a barrier for ethnic and racial minorities. We prospectively evaluated receipt of 8/8 HLA-allele matched URD or either 7/8 URD or cord blood (CB) transplants by patient ancestry from 2005 to 2017. Matched URDs were given priority if they were available. Of 1312 patients, 723 (55%) received 8/8 URD, 219 (17%) 7/8 URD, 319 (24%) CB, and 51 (4%) had no 7/8 or 8/8 URD or CB graft. Europeans were more likely to receive an 8/8 URD transplant than non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 21 publications
2
65
1
Order By: Relevance
“…37,38 Importantly, our observation permits conducting dCBT in patients without well HLA-matched units, especially for many patients of mixed or non-European ancestry. 34,39 Additionally, MRD did not adversely impact PFS of leukemia patients supporting a robust CB-mediated graft-versus-leukemia effect as previously reported. 3,40 Very promising PFS was also observed in AML patients with high relapse risk according to their ELN classification at diagnosis and those with FLT3 ITD.…”
Section: Discussionsupporting
confidence: 83%
“…37,38 Importantly, our observation permits conducting dCBT in patients without well HLA-matched units, especially for many patients of mixed or non-European ancestry. 34,39 Additionally, MRD did not adversely impact PFS of leukemia patients supporting a robust CB-mediated graft-versus-leukemia effect as previously reported. 3,40 Very promising PFS was also observed in AML patients with high relapse risk according to their ELN classification at diagnosis and those with FLT3 ITD.…”
Section: Discussionsupporting
confidence: 83%
“…Cord blood (CB) is a valuable alternative hematopoietic stem cell (HSC) source for patients who lack suitable adult donors, especially racial and ethnic minorities. 1,2 Double-unit CB grafts have successfully extended cord blood transplantation (CBT) to larger children and adults, 3 and both single-and doubleunit CBT has been associated with potent graft-versus-leukemia (GVL) effects, 4,5 low rates of chronic graft-versus-host disease (GVHD), [6][7][8] and high rates of disease-free survival in patients with hematologic malignancies. [4][5][6]8,9 CBT, however, has also been associated with delayed immune reconstitution compared with T-cell replete HLA-matched adult donor allografts with multiple reports of high infection rates early posttransplant.…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, an NMDP study found that while 75% of patients who self-identify as White-European found a donor with 7/8 HLA matching, only 16% for African-Americans found a match (8). A Memorial Sloan Kettering Cancer Center study of 7/8 or 8/8 HLA matching found that 78% of patients with Northwestern European ancestry found a donor, while this number fell to 44% for those with South European ancestry and 22% for those with African ancestry (13). Theoretical studies by Bergstrom et al (11,14) also found that the probability of not finding a match in the NMDP is highest among African-Americans, when compared to other groups.…”
Section: Introductionmentioning
confidence: 99%
“…This scenario may be critical in the case of admixed populations, which trace their ancestry to different geographic regions, and has been the focus of several recent studies on how ethnicity influences the probability of finding a donor ( 8 , 11 13 ). In the USA, an NMDP study found that while 75% of patients who self-identify as White-European found a donor with 7/8 HLA matching, only 16% for African-Americans found a match ( 8 ).…”
Section: Introductionmentioning
confidence: 99%